Barriers and facilitators to breastfeeding support practices in a neonatal intensive care unit in Colombia - Haley Abugov; Sandra Catalina Ochoa Marín; Sonia Semenic; Isabel Cristina Arroyave (Investigación y Educación en Enfermería, 2021)
Objective. To assess breastfeeding support practices and related barriers and facilitators in a large Intensive Care Unit, Neonatal (NICU) in Medellín, Colombia, as part of a broader quality improvement initiative to enhance breastfeeding support.